2022
DOI: 10.1017/qpb.2022.19
|View full text |Cite
|
Sign up to set email alerts
|

Skotomorphogenesis exploits threonine to promote hypocotyl elongation

Abstract: Mobilisation of seed storage reserves is important for seedling establishment in Arabidopsis. In this process, sucrose is synthesised from triacylglycerol via core metabolic processes. Mutants with defects in triacylglycerol-to-sucrose conversion display short etiolated seedlings. We found that whereas sucrose content in the indole-3-butyric acid response 10 (ibr10) mutant was significantly reduced, hypocotyl elongation in the dark was unaffected, questioning the role of IBR10 in this process. To dissect the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Genetic studies of the TAG-to-Suc pathway identified several key enzymes whose loss-of-function affected seedling establishment with varying levels of penetrance ( Hayashi et al., 1998 ; Hooks et al., 1999 ; Froman et al., 2000 ; Eastmond et al., 2000 ; Germain et al., 2001 ; Footitt et al., 2002 ; Rylott et al., 2003 ; Fulda et al., 2004 ). To evaluate the link between TAG-to-Suc conversion and CCE, we phenotypically characterized icl-2 , mls-2 , pck1-2 ( Takahashi et al., 2017 ), and ibr10 mutants ( Tabeta et al., 2021 ; Tabeta et al., 2022 ), all of which displayed class II CCE ( Katano et al., 2016 ; Takahashi et al., 2017 ; Tabeta et al., 2021 ). Hence, producing Suc from TAG during seed germination is crucial for proper cotyledon development.…”
Section: Fugu5 -Mediated Class II Compensation: Contribution...mentioning
confidence: 99%
“…Genetic studies of the TAG-to-Suc pathway identified several key enzymes whose loss-of-function affected seedling establishment with varying levels of penetrance ( Hayashi et al., 1998 ; Hooks et al., 1999 ; Froman et al., 2000 ; Eastmond et al., 2000 ; Germain et al., 2001 ; Footitt et al., 2002 ; Rylott et al., 2003 ; Fulda et al., 2004 ). To evaluate the link between TAG-to-Suc conversion and CCE, we phenotypically characterized icl-2 , mls-2 , pck1-2 ( Takahashi et al., 2017 ), and ibr10 mutants ( Tabeta et al., 2021 ; Tabeta et al., 2022 ), all of which displayed class II CCE ( Katano et al., 2016 ; Takahashi et al., 2017 ; Tabeta et al., 2021 ). Hence, producing Suc from TAG during seed germination is crucial for proper cotyledon development.…”
Section: Fugu5 -Mediated Class II Compensation: Contribution...mentioning
confidence: 99%
“…Peak areas were normalized using a quality control sample and the LOWESS/Spline normalization tool (Tsugawa et al, 2014a). Detailed GC-QqQ-MS parameters and MRM transitions for wide-target analysis were previously described (Tabeta et al, 2021;Tabeta et al, 2022).…”
Section: Wide-target Metabolome Analysis Of Gc-qqq-msmentioning
confidence: 99%
“…The residue was dissolved in 250 μL of ethanol and centrifuged at 10,000 × g for 15 min. The supernatant was subjected to LC-MS/MS analysis 75 . The dataset was analyzed using MS-DIAL version 4.80.…”
Section: Lipidome Analysis Using Lc-qtof-msmentioning
confidence: 99%
“…Calculation and normalization of peak area values were conducted using MRMPROBS and LOWESS/Spline normalization tools as described previously 73 . Detailed GC-MS/MS parameters 74 and MRM transitions 75 for widely targeted analysis have been previously described.…”
Section: Widely Targeted Metabolome Analysis Using Gc-qqq-msmentioning
confidence: 99%